2014
DOI: 10.3892/mmr.2014.2151
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide induces autophagy via ATM-AMPK-ULK1 pathways in glioma

Abstract: Abstract. Autophagy is a cytoprotective process, which occurs following temozolomide (TMZ) treatment, and contributes to glioma chemoresistance and TMZ treatment failure. However, the molecular mechanisms by which TMZ induces autophagy are largely unknown. In the current study, the ataxia-telangiectasia mutated (ATM) inhibitor KU-55933, adenosine monophosphate-activated protein kinase (AMPK) inhibitor compound C, and U87MG and U251 cell lines were employed to investigate the molecular mechanisms of TMZ-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 21 publications
5
48
0
Order By: Relevance
“…Autophagy is an alternative program of cell death that may be initiated to overcome the resistance of gliomas to apoptosis. Indeed, TMZ has been reported to exert cytotoxicity by induction of autophagy in malignant glioma cells [27,40]. Our data reveal that like TMZ, analogs 1 and 2 induced autophagy in U87MG cells.…”
Section: Discussionsupporting
confidence: 52%
“…Autophagy is an alternative program of cell death that may be initiated to overcome the resistance of gliomas to apoptosis. Indeed, TMZ has been reported to exert cytotoxicity by induction of autophagy in malignant glioma cells [27,40]. Our data reveal that like TMZ, analogs 1 and 2 induced autophagy in U87MG cells.…”
Section: Discussionsupporting
confidence: 52%
“…[30][31][32] Accumulating evidence has unveiled the complex crosstalk between DDR pathways and autophagy. Activation of ATM [33][34][35][36] by various insults induces autophagy, and TP53 [37][38][39] and MTOR 35,36,[39][40][41] are 2 representative downstream signaling nodes connecting the DDR pathways to autophagy. The descriptions of autophagy regulation by ATR are rather scarce, but there is strong evidence showing that ATR is a potential upstream regulator of autophagy.…”
Section: Three Classes Of Ptdins3k and Pi3k Enzymesmentioning
confidence: 99%
“…TMZ induces autophagy in other ways (25). Zou et al (26) identified that TMZ inhibited the growth of glioma cells and decreased the number of cells in S and G 2 /M, leading to atypical cell apoptosis. The present study identified that the use of TMZ alone to treat U251 cells induces a slight increase in autophagy-related proteins and may induce the apoptosis of glioma cells to a certain extent, which is consistent with a previous study (15).…”
Section: Discussionmentioning
confidence: 99%